Drug-drug interaction between ensitrelvir and tacrolimus in a patient undergoing treatment for COVID-19: a case report - Yuki Miyata; Ryo Yamaguchi; Takehito Yamamoto; Toshiyuki Kishida; Kazuhiko Ikeuchi; Hiroaki Harada; Takeya Tsutsumi; Keishi Fujio; Tappei Takada (Journal of Pharmaceutical Health Care and Sciences, 2025)
Abstract Background Ensitrelvir is a novel SARS-CoV-2 3-chymotrypsin-like protease inhibitor, similar to nirmatrelvir/ritonavir. Several case reports have demonstrated the efficacy of 3-chymotrypsin-like protease inhibitors in treating prolonged coronavirus disease 2019 (COVID-19) in immunocompromised patients. Tacrolimus (TAC) is a widely used immunosuppressive agent whose blood level can increase significantly due to the inhibition of cytochrome P450 3A (CYP3A) and P-glycoprotein by nirmatrelvir/ritonavir. Since ensitrelvir also inhibits CYP3A and P-gp, similar elevations in TAC levels are expected. A prior case report observed an increase in TAC trough levels with concurrent administration of ensitrelvir. However, no studies have quantitatively described the changes in TAC blood levels and clearances before and after ensitrelvir administration when TAC administration was discontinued to mitigate the drug-drug interaction (DDI) risk; data on safe dosing protocols to avoid the DDI during co-administration of ensitrelvir and TAC remain lacking. Here, we report a case in which TAC levels were successfully managed in a patient with rheumatoid arthritis (RA) who received ensitrelvir for persistent COVID-19 by preemptive discontinuation of TAC and close monitoring of TAC blood levels following ensitrelvir administration. Case presentation An 81-year-old Japanese woman who had been administered TAC (1.5 mg once daily) for RA received two courses of remdesivir for moderate COVID-19. However, her viral load remained high and her respiratory status deteriorated. Considering persistent COVID-19, we initiated combination therapy with remdesivir and ensitrelvir (day 0). TAC was discontinued, and the TAC blood levels decreased from 3.6 ng/mL to 1.1 ng/mL over five days. Subsequently, we re-administered TAC (0.2 mg), observing a level of 1.0 ng/mL by day 7. The TAC dose was adjusted to 1.0 mg daily, and TAC levels on day 12 and 14 were 6.5 and 3.7 ng/mL, respectively. TAC (1.5 mg daily) was resumed on day 15. The calculated t1/2 of TAC were 33.7, 71.9, and 114.6 h from day -1 to 0, day 0 to 2, and day 2 to 5, respectively. The t1/2 of TAC was extended to 3.4-fold its original duration under ensitrelvir treatment. Conclusions This DDI extended the half-life of TAC by approximately 3.4-fold, an effect that gradually diminished over 7 to 10 days. When patients receiving TAC treatment start ensitrelvir therapy, a dose reduction of TAC by approximately one-third to one-fourth is considered appropriate.